1985
DOI: 10.2307/4086848
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contribution of the Sexes to Prefledged Young in Red-Throated Loons

Abstract: is no obvious leader. Any intermediate echelon will suffice for purposes of visual communication, as long as its angle is not so acute as to put following birds in the blind area. A V is two echelons joined at the apex, and it is perhaps not surprising that echelon flight is common, while V-formation flight is not. If there is functional advantage to the V, it is evidently not of great significance. We thank Charles Alien of the Rhode Island Department of Environmental Management for providing the goose heads,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
0
14
2
Order By: Relevance
“…Our results concerning parental investment are to some extent contradictory to what Reimchen & Douglas (1985) reported from British Columbia. They found that the female made significantly more foraging trips but brought smaller fish to the nesting site.…”
Section: Parental Investment In Foragingcontrasting
confidence: 99%
“…Our results concerning parental investment are to some extent contradictory to what Reimchen & Douglas (1985) reported from British Columbia. They found that the female made significantly more foraging trips but brought smaller fish to the nesting site.…”
Section: Parental Investment In Foragingcontrasting
confidence: 99%
“…Norberg 1976, Eriksson et al 1990). Because many fish (7-14) are fed to each chick daily (Reimchen and Douglas 1985, Dickson 1992, Eriksson et al 1990, foraging flights are frequent, making them costly in time and energy (Norberg and Norberg 1971, 1976, Davis 1972). Often only one of the two chicks is raised to fledging.…”
Section: Reproductive Success Of Birds Is Usually Determined By the Amentioning
confidence: 99%
“…First, foraging adults may not be capable of delivering enough fish to both young, resulting in starvation-related mortality of chicks. Second, adults may maintain an adequate feeding frequency at the expense of time spent guarding and defending chicks against predators, increasing predator success (Fagerstr•Sm et al 1983, Reimchen andDouglas 1985).…”
Section: Reproductive Success Of Birds Is Usually Determined By the Amentioning
confidence: 99%
“…Parker (1988) and Alvo et al(1988) sampled potential prey in waters frequented by loons, attempting to relate variety and abundance of prey to reproductive success and effects of man-induced acidification . Reimchen & Douglas (1985) calculated food consumption and requirements of Red-throated Loon (Gavia stellata) chicks from estimated sizes of fish carried by parents and the number of successful foraging flights .…”
Section: Introductionmentioning
confidence: 99%